Animal models for human herpesvirus 6 infection - Reynaud, Joséphine; Horvat, Branka (Frontiers in Microbiology, 2013)
Human herpesvirus (HHV)-6A and HHV-6B are two enveloped DNA viruses of β-herpesvirus family, infecting over 90% of the population and associated with several diseases, including exanthema subitum (for HHV-6B), multiple sclerosis and encephalitis, particularly in immunosuppressed patients. Animal models are highly important to better understand the pathogenesis of viral infections. Naturally developed neutralizing antibodies to HHV-6 or a related virus were found in different species of monkeys, suggesting their susceptibility to HHV-6 infection. Both HHV-6 DNA and infectious virus were detected in experimentally infected Cynomolgus and African green monkeys, although most animals remained clinically asymptomatic. Furthermore, HHV-6A infection was shown to accelerate the progression of AIDS in macaques and to lead to the development of neurological symptoms in the marmoset model. Humanized SCID mice efficiently replicated HHV-6 and were also susceptible to coinfection with HHV-6 and HIV-1. As CD46 was identified as a receptor for HHV-6, transgenic mice expressing human CD46 may present a potentially interesting model for study certain aspects of HHV-6 infection and neuroinflammation.